ANTIDIABETIC ACTIVITY TEST OF BITTER GOURD EXTRACT (Momordica charantia) AS AN INHIBITOR OF α - GLUCOSIDASE ENZYME BY IN SILICO - Kezya Wowor; Widdhi Bodhi; Olvie Datu; Axl Windah (PHARMACON, 2022)
ABSTRACTDiabetes mellitus (DM) is a metabolic disorder that interferes with the metabolism of carbohydrates, fats, and proteins. This study aims to determine the types of bioactive compounds contained in bitter melon extract and to analyze interaction of targeted compounds against the α -glucosidase enzyme using the in silico approach. The results of the analysis using Gas Chromatography- Mass Spectrometer (GCMS) used to obtain information on bioactive compounds that will be used as ligands to be attached to the α-glucosidase enzyme. Furthermore, the potential ability of each compound as antidiabetic was test using PyRx application and Acarbose was its control. The results of the GCMS analysis of this study contained 23 compounds detected in the methanol extract of bitter melon. This research proves that the compound Spirost-8-en-11 one, 3 hydroxy, (3ß,5a,14ß, 20ß, 22ß, 25R) with a binding affinity of -9.0 kcal/mol and Cholesta-8,24-dien -3-ol, 4-methyl-, (3ß,4a)- with a binding affinity of -8.3 kcal/mol have a good conformation. This research can be concluded that the two compounds can be developed as antidiabetic.  Keywords: Bitter Melon (Momordica charantia), antidiabetic, α - Glucosidase enzyme, molecular docking